Famine - Strasser, Theo; Henderson, Graham, 1953-; Anajah Press ([Melbourne] : Anajah Press, 2017)
Famine is a little zine with poetry by Graham Henderson and art work by Theo Strasser. The writing has been taken from the Henderson's The Quiros Suite: Famine, a collection of poems published by The Lovers Press, Melbourne, 2016.
Artist's book. Digitally printed pages, with hand-painted and hand-printed covers and end papers..
Limited edition of 55 copies.
National Library's SR copy is no. 40/55, signed by both the artist and author.
Keywords: Artists' books -- Victoria; Famines -- Pictorial works; Poetry and the arts; Australian; Zines